Geoheritage assessment of Gua Sireh, Baling, Kedah. Issue 1 (August 2021) - Sulaiman, N; Sulaiman, N; Roslan, N F; Mohd Sabari, N S; Abdullah, N
Abstract: Gua Sireh is located in Baling, Kedah, Malaysia. Baling is a district that hold a variety of unique and beautiful geological features with geoheritage values and attractive geological landforms. The Gua Sireh is currently conserved by the Kampung Padang Che Mas's committee members as a part of their tourism site. The aim of this paper is to formally evaluate the potential geoheritage values of Gua Sireh as a geoheritage resources using the classification, assessment and evaluation methods. Based on this study, five geoheritage values had been identified in Gua Sireh, which are scientific/educational, aesthetic, recreational, historical/cultural and economic values. The scale of this geosite is small to medium, and the level of significance is local to state. By this initiative, it is hope that Gua Sireh can be preserved from any threats and continues to develop in order to sustain and protect the geological features while supporting the geotourism development in the state of Kedah.